Compliance with preoperative care measures reduces surgical site infection after colorectal operation. Issue 4 (24th December 2018) - Guzman‐Pruneda, Francisco A.; Husain, Syed G.; Jones, Christian D.; Beal, Eliza W.; Porter, Erica; Grove, Michele; Moffatt‐Bruce, Susan; Schmidt, Carl R.
Abstract : Background: Surgical site infections (SSIs) are a major cause of morbidity complicating colorectal operations. Several evidence‐based preoperative strategies are associated with decreased SSI rates. We hypothesize that compliance with multiple strategies is associated with lower incidence of SSI after the elective colorectal operation. Methods: Preoperative care measure compliance before colorectal operations were assessed. Measures included antiseptic wash the night before and day of operation, oral antibiotic, and mechanical bowel preparation, antibiotic prophylaxis, Chloraprep skin preparation, and hair clipping. Rates of SSI after colectomy and other pertinent outcomes were stratified by full and partial compliance with preoperative measures. Exclusion criteria included bowel perforation, ischemia, complete obstruction, intra‐abdominal abscess, and no intraoperative skin closure. Results: Eight hundred twenty‐six subjects underwent colectomy between 2010 and 2016; 469 met inclusion criteria. Compliance with all measures occurred in 214 (46%) and was independently associated with lower postoperative infection rates (odds ratio [OR], 0.37; confidence interval [CI], 0.16‐0.85; P = 0.02). SSI occurred in 51 (11%): was superficial in 35 (7%); deep in 5 (1%); and organ space in 11 (2%). SSI rates were reduced from 16% (partial or no compliance group) to 5% (full compliance group). No stand‐alone intervention was independently associated with decreased SSI rate. Multivariate analysis found the following factors associated with a lower risk of SSI: full compliance with all five process measures, lower BMI, nonsmoker, and minimally invasive operation. Discussion and Conclusion: Compliance with preoperative care strategies reduces rates of SSI after colectomy with a cumulative effect more pronounced than any single intervention reinforcing the need for protocol‐driven and evidence‐based care for patients undergoing colorectal operations.